Progressing towards climate resilient agriculture: top ten success stories from CCAFS in South Asia - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The top ten success stories from CCAFS in South Asia presented in this document, exhibit evidence on how agriculture can be transformed to become resilient and productive, thereby, protecting the farming systems from the hazards of climate change. In addition to these ten success stories, this document also includes ten other successes and emerging stories that highlight some of the significant work being undertaken, some of which have established outcomes and some other, expected to lead to positive accomplishments in the near future.